2007
DOI: 10.1063/1.2454512
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of an amorphous carbon tunnel diode

Abstract: Negative differential conductance in metal/amorphous nitrogenated carbon ͑a-CN x ͒ / Si structures is demonstrated at room temperature. These metal-insulator-semiconductor tunnel diodes are fabricated by optimizing the tunnel barrier at the a-CN x / Si junction through the control of the band gap and nitrogen doping level in carbon where this a-C layer acts as a semi-insulator. A small electron tunneling effective mass of about 0.06 times the free electron mass, a coherence length of ϳ10 nm in these thin a-CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In this way, a-CN x thin films are now being considered as a possible material to extend the applications of amorphous carbon materials which have presented limited success in electronic devices (OLEDs, TFTs…). The performance of such devices depends on the electronic properties of the films [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, a-CN x thin films are now being considered as a possible material to extend the applications of amorphous carbon materials which have presented limited success in electronic devices (OLEDs, TFTs…). The performance of such devices depends on the electronic properties of the films [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Keay et al have observed NDR behavior in GaAs superlattice structures and suggested that it occurs due to alignment and misalignment of sub band states under applied voltage. For carbon-based materials, Bhattacharyya and Silva have also found NDR behavior at room temprature for a-CN x /Si heterostructures, which becomes prominent at 80 K.…”
Section: Resultsmentioning
confidence: 91%
“…6 Nevertheless, there have been efforts to establish the superior nano-electronic properties of nitrogen incorporated carbon heterostructures and related devices. [7][8][9] Although some interesting transport properties from the nitrogen incorporated carbon devices were observed, progress has been hindered by a limited understanding of the electronic transport mechanism in these structures. In general, the complex nature of defects in a À C and amorphous nitrogenated carbon (a À CN) films and their specific role in the possible enhancement of the electronic transport appear to be unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…We think that the previously discussed models of disorder should have been extended for explaining quantum transport in a carbon system which could show the features of resonant tunneling. 5,7 Hence, it is fundamentally important to develop a microstructural model of a À C films based on the local distortion of sp 2 À C to sp 3 À C structures and the deformation potential of the respective bonds. 30 In multi-layered GaAs structures, the effect of disorder was shown by adjusting the hopping parameters and adding random potential fluctuations.…”
Section: Introductionmentioning
confidence: 99%